2010
DOI: 10.1017/s1743921311000457
|View full text |Cite
|
Sign up to set email alerts
|

Observations of star formation triggered by H ii regions

Abstract: Abstract. Observations show that expanding H ii regions may trigger star formation. We discuss several aspects of this type of star formation, and try to estimate its prevalence. We show how LMC H ii regions may help us to understand what we see in our Galaxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This prediction differs from the observed stellar content of OB associations (Garmany, 1994;Massey, 2003), which show a fully populated stellar IMF within their sub-clusters (de Geus, 1992;Preibisch & Zinnecker, 1999;Brice ño et al, 2007). Nevertheless, observations of HII bubbles do suggest a causal relation between the first generation of stars located in the bubble and the second generation of embedded clusters located at its rim (Deharveng & Zavagno, 2011).…”
Section: The Formation Of Unbound Systemsmentioning
confidence: 98%
“…This prediction differs from the observed stellar content of OB associations (Garmany, 1994;Massey, 2003), which show a fully populated stellar IMF within their sub-clusters (de Geus, 1992;Preibisch & Zinnecker, 1999;Brice ño et al, 2007). Nevertheless, observations of HII bubbles do suggest a causal relation between the first generation of stars located in the bubble and the second generation of embedded clusters located at its rim (Deharveng & Zavagno, 2011).…”
Section: The Formation Of Unbound Systemsmentioning
confidence: 98%
“…Thus, sequential star groups and stellar populations in a turbulent cloud cannot easily be observationally recognised unless very accurate age measurements are possible. Nevertheless, the observational evidence for ongoing triggered star formation near massive stars has been growing recently (for an updated list, see Deharveng & Zavagno 2011). Numerical simulations as well (e. g., Dale et al 2012b) have shown that triggered star formation does occur in giant molecular clouds as a result of ionising feedback (and molecular outflows) from massive stars, although this feedback also tends to result in a globally lower star-formation efficiency.…”
Section: Introductionmentioning
confidence: 99%